Analysis of Landslide Vulnerability Levels in Maligano District - Deti Krisnawati; Noor Husna Khairisa (JAGAT (Jurnal Geografi Aplikasi dan Teknologi), 2024)
Landslides are one of the natural disasters that frequently occur in Indonesia, particularly in regions with hilly geographical conditions and steep slopes, such as in Maligano District, Muna Regency. This study aims to analyze the landslide susceptibility in Maligano District using scoring and overlay methods. The research examines various variables, including land use, slope gradient, rainfall, soil type, and rock type. The results show that Maligano District has three categories of landslide susceptibility levels: low (183 hectares), medium (4,646 hectares), and high (6,829 hectares). Langkoroni and Latompa villages are the areas with the largest high susceptibility, covering 2,243 hectares and 1,645 hectares, respectively. The dominant factors influencing susceptibility are steep slopes (25-40%), ranfall 2000-2500mm/y, non-vegetated land use, and vulnerable geological conditions.